Athletics, Music, Languages, and Leadership: How Parents Influence the Extracurricular Activities of their Children - Ashbourne, Dianne; Andres, Lesley (Canadian Journal of Education/Revue canadienne de l’éducation, 2015)
In this study, we explore the impact that parents have on the participation of their children in extracurricular activities (ECAs) in a sample of Canadian parents with children between the ages of four and 17. Employing a concurrent, nested, mixed methods strategy, we use the insights gained through semi-structured interviews with parents to inform the creation of four regression models with which we investigate four types of activities (athletics, music, languages, and leadership). Our findings reveal that, depending on the type of activity, ECA participation by children varies by parental education. Values and experiences held by parents with the lowest educational attainment were stronger predictors of participation in specialized music programs, and those of parents with advanced degrees were stronger predictors of participation by their children in specialized language programs. We conclude by discussing the equity implications of our study for Canadian children.